2022
DOI: 10.1093/jaoacint/qsac123
|View full text |Cite
|
Sign up to set email alerts
|

Green Spectrophotometric Platforms for Resolving Overlapped Spectral Signals of Recently Approved Antiparkinsonian Drug (Safinamide) in the Presence of Its Synthetic Precursor (4-Hydroxybenzaldehyde): Applying Ecological Appraisal and Comparative Statistical Studies

Abstract: Background Safinamide, a highly specific inhibitor of monoamine oxidase B, is a new approved prodigious therapy used to cure Parkinson's disease. Objective Before marketing and selling a medicine, manufacturers must guarantee that the manufacturing process is consistent by monitoring levels of process-related chemicals and drug contaminants. Therefore, five precise, fast, and accurate spectrophotometric techniques were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A thorough review of the literature has identified a number of analytical approaches, such as HPLC 21 26 , HPTLC 27 , UPLC 28 , electrochemical 29 , 30 , and UV-spectrophotometric methods 31 that can accurately quantify SAF alone or in combination with other drugs. To our knowledge, there is currently no eco-friendly spectrofluorimetric method for determining SAF in the presence of its related impurity.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of the literature has identified a number of analytical approaches, such as HPLC 21 26 , HPTLC 27 , UPLC 28 , electrochemical 29 , 30 , and UV-spectrophotometric methods 31 that can accurately quantify SAF alone or in combination with other drugs. To our knowledge, there is currently no eco-friendly spectrofluorimetric method for determining SAF in the presence of its related impurity.…”
Section: Introductionmentioning
confidence: 99%